Alternatif Pendanaan Antara Leasing, Hutang Jangka Panjang dan Saham Biasa dalam Pengadaan Aktiva Tetap pada PT. Blue Bird Tbk - Mei Mita Bella; Evaliati Amaniyah (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
In a business, fixed assets are very important for a company, fixed assets in the company are usually used as an investment for the long term. In addition, the most important thing in a company is fixed assets as a working capital for the survival of the company. The choice of financing alternatives will affect the decision making in the procurement of fixed assets. The purpose of this study is to determine which source of funding is the most efficient in the procurement of fixed assets among leasing, long term debt, and common stock capital at PT. Blue Bird Tbk in 2019. This study uses a descriptive research method that compare   net present value of the three funding alternatives. The result of study shows that long-term debt has a smallest net present value compared to leasing and common stock capital so that it is most efficient when used in the procurement of fixed assets in PT. BIue Bird Tbk.